Comparison of modelling techniques for assessment of spillways. Issue 3 (12th July 2019) - Green, James
Abstract : Theoretical equations, computational fluid dynamics (CFD) and physical modelling are the three main commonly and commercially used techniques to analyse the performance of current or proposed dam spillways. The purpose of this paper is to compare the aforementioned modelling techniques, and ascertain the most appropriate application for pertinent features commonly required for analysis on a typical spillway. My employment allows me the unique opportunity to explore each technique with a critical analysis of individual performance and accuracy. It also allows me access to a great deal of physically modelled dam spillway data, against which to validate the CFD model to ensure accuracy. The paper will study each technique if applicable for the following pertinent requirements: Q/H curve, out-of-channel flow, velocity profiles, energy dissipation, pressure and hydraulic profile.